2019
DOI: 10.1186/s12935-019-1011-y
|View full text |Cite
|
Sign up to set email alerts
|

Circ_ZNF124 promotes non-small cell lung cancer progression by abolishing miR-337-3p mediated downregulation of JAK2/STAT3 signaling pathway

Abstract: Background: Previous genome-wide transcriptome profiling found circ_ZNF124 was highly expressed in lung adenocarcinoma, however, the role of circ_ZNF124 in non-small cell lung cancer (NSCLC) is still unknown. The purpose of this study was to investigate the role and molecular mechanism of circ_ZNF124 in NSCLC development. Methods: The expression of circ_ZNF124, miR-337-3p and JAK2 (Janus Kinase 2) in lung cancer cell lines and normal epithelial cells were detected by qRT-PCR (quantitative real-time PCR). siRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…24 Circ_ZNF124 contributed to NSCLC progression by targeting miR-337-3p/JAK2/ STAT3 signaling. 25 Zhang et al found that circ_SATB2 accelerated NSCLC progression through acting as miR-326 sponge to up-regulate FSCN1 expression. 15 Here, we found that circ_SATB2 was highly expressed in NSCLC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…24 Circ_ZNF124 contributed to NSCLC progression by targeting miR-337-3p/JAK2/ STAT3 signaling. 25 Zhang et al found that circ_SATB2 accelerated NSCLC progression through acting as miR-326 sponge to up-regulate FSCN1 expression. 15 Here, we found that circ_SATB2 was highly expressed in NSCLC tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, correlation heat map indicated that the nine genes were highly relevant to miR-337-3p ( Fig. 4c) and STAT3 was selected for further study as previous evidence proved that it was targeted by miR-337-3p 29,30 , and played a crucial role in EMT 31 .…”
Section: Mir-337-3p Mediated Emt In 4t1 Cells By Directly Targeting Smentioning
confidence: 99%
“…Another study reports that circ‐FGFR1 overexpression enhances migration, invasion, proliferation and immune evasion in vitro as well as promotes resistance to anti‐PD‐1 treatment in vivo in NSCLC 21 . In addition, circ‐ZNF124 provokes growth, the arrest in sub‐G1 phase of cell cycle, migration, and colony formation of NSCLC cells through abrogating the decrease of Janus tyrosine kinase‐2/signal transducer and activator of transcription 3 (JAK2/STAT3) signaling pathway regulated by miR‐337‐3p 22 . And circ‐PIP5K1A enhances proliferation and metastasis in mice model of NSCLC by mediating miR‐600/HIF‐1α signaling 13 .…”
Section: Discussionmentioning
confidence: 99%